PERSEPSI MAHASISWA MAGISTER AKUNTANSI TERHADAP PEMAHAN KODE ETIK AKUNTAN PADA PERGURUAN TINGGI SWASTA DI JAKARTA - Bertha Elvy Napitupulu (JURNAL MITRA MANAJEMEN, 2015)
ABSTRACT The purpose of these research are to know different of accounting student magister’s perception faced toethic of conduct’s accountant profession understanding based on, level of student ( Semester), Cumulative Achievement (IPK), Status of the job.In this research, the variables are accounting Students Magister’ perception, ethics codes understanding,and accountant profession. The aim of this research is to find empirical evidence about how far is thestudents’ understanding in accountant ethics codes. The method that used in this research is t tesdifferent analysis technique.Research population is Magister accounting students in eight (8) Particullary University in Jakarta Datasampling was calculated based on non probability sampling or purposive and collection method is mailquestionaire, sent 200 questionaire and received 65 and 60 questionaire processed. Statistical test inthis research are data quality test, classical assumption test and hypothesis test.Result of research are: (1) auditor competence proven influence significantly on audit quality, (2) auditorindependence influence significanly on audit quality, (3) auditor competence and auditor independencesimultantly influence significantly on audit quality.Keywords: the accountant students Magister’s perceptions, ethics codes of accountantprofessional, scope of ethics contents.